ANALISIS DAYA SAING INDUSTRI HALAL DALAM PENGEMBANGAN INOVASI PRODUK HALAL DI INDONESIA: ANALISIS DATA SEKUNDER - Helga Mai Fransiska helga; Desmi Satriana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The Indonesian halal industry has significant potential to compete in the global market, supported by increasing demand for halal products and consumer awareness. This study analyzes the competitiveness of the halal industry in driving innovation in products that comply with Islamic law, using a qualitative descriptive approach based on secondary data from government reports and previous research. The study results indicate that the competitiveness of the Indonesian halal industry is influenced by government regulations, halal certification, the innovation capacity of industry players, and a supportive halal ecosystem. Despite its superior Muslim population and large domestic market, Indonesia still faces challenges in technology and research and development. Therefore, synergy is needed between the government, business actors, and supporting institutions to increase the competitiveness of Indonesian halal products on the global stage.